Educational reform and disadvantaged students : are they better off or worse off? - John H. Bishop; Ferran Mane (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper analyzes the effects of increased academic standards on both average achievement levels and on equality of opportunity. The five policies evaluated are: (1) universal Curriculum-Based External Exit Exam Systems, (2) voluntary curriculum-based external exit exam systems with partial coverage such as New York State Regents exams in 1992, (3) state minimum competency graduation tests, (4) state defined minimums for the total number of courses students must take and pass to get a high school diploma and (5) state defined minimums for the number of academic courses necessary to get a diploma. We use international data to evaluate the effects of CBEEES. High school graduation standards differ a lot across states in the U.S. This allowed us to measure policy effects on student achievement and labor market success after high school by comparing states in a multiple regression framework. Our analysis shows that only two of the policies examined deliver on increasing everyone's achievement and also reduce achievement gaps: universal CBEEES and higher academic course graduation requirements. Other policies were less successful in raising achievement and enhancing equality of opportunity.
Keywords: I2; H5; 330; Bildungsreform; Bildungsniveau; Bildungschancen; Bildungsertrag; Leistungskontrolle; Schätzung; Vereinigte Staaten; Zentralexamen